An Open Letter to Norman Cantor Regarding Dementia and Physician-Assisted Suicide - Sulmasy, Daniel P. (The Hastings Center report, 2018)
Dear Norm, Thank you for sharing such a personal and heartfelt essay. I have been asked by the editors to comment. Reading it inspires me to do so in a similarly heartfelt way. Although I don't know you well, I thought I'd write to you as if you were my patient. I share your sense that Alzheimer disease is a terrible scourge. I've seen much of this disease over a lifetime of practice, and I deeply understand its ravages and the debility and suffering it causes. But what you propose is not a good solution for the problems that Alzheimer disease poses for patients, families, and society. It will ultimately do far more harm than good. Please let me try to explain.